Cellular Senescence and Senotherapies in the Kidney: Current Evidence and Future Directions - Docherty, Marie Helena; Baird, David P.; Hughes, Jeremy; Ferenbach, David A. (Frontiers in Pharmacology, 2020)
Cellular senescence refers to a cellular phenotype characterised by an altered transcriptome, pro-inflammatory secretome and generally irreversible growth arrest. Acutely senescent cells are widely recognised as performing key physiological functions in vivo promoting normal organogenesis, successful wound repair and cancer defence. In contrast, the accumulation of chronically senescent cells in response to aging, cell stress, genotoxic damage and other injurious stimuli is increasingly recognised as an important contributor to organ dysfunction, tissue fibrosis and the more generalised aging phenotype. In this review we summarise our current knowledge of the role of senescent cells in promoting progressive fibrosis and dysfunction with a particular focus on the kidney and reference to other organ systems. Specific differences between healthy and senescent cells are reviewed along with a summary of several experimental pharmacological approaches to deplete or manipulate senescent cells to preserve organ integrity and function with ageing and after injury. Finally, key questions for future research and clinical translation are discussed.